Research geothermal greenhouses - Opryshko, O.; Pasechnik, N.; Zubkov, I. (Energy and Automation, 2015)
The estimation of the thermal area of experimental geo-heleotermalnoyi greenhouses to determine the optimal height suspension trays of seedlings. Tested effectiveness of the proposed design greenhouses in spring.